Developing PCK Assessment Instruments to Measure Teaching Competence in Arts and Culture Programs - Sayekti, Pranti (Angstrom Centre of Education, 2025)
This study aims to develop an assessment instrument for Pedagogical Content Knowledge (PCK) to evaluate the teaching competence of students in the Arts and Culture Teacher Professional Education Program (PPG) at Universitas Negeri Malang. PCK, combining content knowledge and pedagogy, is essential for effective teaching. The research follows a research and development (R&D) method, including needs analysis, design, development, validation, and testing. Data collection involved questionnaires, interviews, and classroom observations. Experts validated the instrument for accuracy and relevance, while trials with PPG students tested its reliability and validity. The results show high validity and reliability, with the instrument assessing learning planning, implementation, and evaluation. It helps measure students' competence and serves as a self-reflection tool to improve teaching quality. The instrument contributes to enhancing teacher education, particularly in arts and culture, and supports efforts to increase teacher professionalism in Indonesia.